Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
Given: f(1)= f(3) = 0
Putting f(1) = a(1)^2 + b(1) + c
= a + b + c
Putting f(3) = a(3)^2 + b(3) + c
= 9a + 3b + c
Putting f(0)=a(0)^2 + b(0) + c = -3
= c = -3
putting c = -3 In equation (1) and equation (2) we get,
a + b - 3 = 0 9a + 3b - 3 = 0
a + b = 3 3(3a+b) = 3
a = 3 - b 3a + b = 1
3(3-b) + b = 1 [Putting a = 3 - b ]
9 - 3b +b = 1
-2b = -8
b = 4
Answer:
b = 4
Step-by-step explanation:
To find the value of b in the quadratic function f(x) = ax² + bx + c, begin by substituting f(0) = -3, and solve for c:
[tex]f(0) = -3\\\\a(0)^2+b(0)+c=-3\\\\0+0+c=-3\\\\c=-3[/tex]
Substitute c = -3 into the function:
[tex]f(x) = ax^2+bx-3[/tex]
Now, substitute f(1) = 0 and f(3) = 0 into the function to form a system of equations:
[tex]f(1)=0\\\\a(1)^2+b(1)-3=0\\\\a+b-3=0[/tex]
[tex]f(3)=0\\\\a(3)^2+b(3)-3=0\\\\9a+3b-3=0[/tex]
So, the system of equations is:
[tex]\begin{cases}a+b-3=0\\9a+3b-3=0\end{cases}[/tex]
Rearrange the first equation to isolate a:
[tex]a+b-3=0\\\\a=3-b[/tex]
Substitute a = 3 - b into the second equation and solve for b:
[tex]9(3-b)+3b-3=0\\\\27-9b+3b-3=0\\\\24-6b=0\\\\6b=24\\\\b=4[/tex]
Therefore, the value of b is:
[tex]\Large\boxed{\boxed{b=4}}[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.